Brand South Africa : Dutch impressions of the ‘Rainbow Nation’ - Freemantle, Simon Arthur Christopher (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MA (Political Science))--University of Stellenbosch, 2007.